The Sinters of the Ohaki and Champagne Pools, New Zealand: Possible Modern Analogues of the Hemlo Gold Deposit, Northern Ontario - Goldie, Raymond (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1985)
Summary The Archean Hemlo gold deposit has many similarities with the sinters formed by two New Zealand hot springs, the Ohaki and Champagne pools. The New Zealand hot springs, therefore, warrant consideration as possible analogues of the mineralizing system which formed the Hemlo deposit. The waters which issue from the Ohakiand Champagne pools are ultimately of meteoric origin. These waters have passed to depths of at least 1.5 km in a complex sequence of volcanic and sedimentary rocks, and have returned to the surface as neutral, weakly saline fluids near their boiling points. These fluids are undersaturated, by several orders of magnitude, with respect to the gold they contain, At the surface the fluids are cooled, oxidized and acidified, causing them to precipitate much of their dissolved load. The precipitated material forms aprons of siliceous sinter richin sulphur, gold, arsenic, antimony, mercury and thallium.